Gray matter volume and asymmetry in Broca's and Wernicke's area homologs in chimpanzees (Pan troglodytes) using a probabilistic region of interest approach - William D Hopkins; Muhammad A Spocter; Michele M Mulholland; Chet C Sherwood (NeuroImage)
Broca's and Wernicke's areas are comprised of Brodmann areas 44, 45 and 22 in the human brain. Because of their roles in higher cognitive and linguistic function, there has been historical and contemporary interest in comparative studies on the morphology and cytoarchitectonic organization in Broca's and Wernicke's between primate species. One challenge to comparative morphological studies between human and nonhuman primates for Broca's and Wernicke's areas is the absence in homologous sulci used to define these regions. To address this limitation, we created probabilistic atlas maps of BA44, BA45 and BA22 based on previously reported cytoarchitectonic maps of these regions in chimpanzees. We then applied the maps to segmented gray matter volume to estimate gray matter within each region and hemisphere. Females were found to have significantly higher gray matter volumes for BA44 and BA45 compared males. Significant negative associations were found between age and gray matter volume for BA44 and BA45 but not BA22. Population-level asymmetries were found for BA44, BA45 and BA22 but there are some limitations in the interpretation of these findings. Lastly, using quantitative genetic analyses, we found significant heritability in the average gray matter volume for BA44 and BA45 but not BA22. The sex and age effects found in chimpanzees are consistent with previous studies in humans.